Ketidakpastian Ekonomi, Financial Anxiety dan Penurunan Minat Pernikahan Generasi Z dalam Perspektif Ekonomi Islam - Nenis Tri Atikah; Danik Kurnia Sari; Ai Dina Herlina; Budi Jaya Putra (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
The decline in marriage rates in Indonesia in recent years has become an important social phenomenon to study because it is related to changes in the behavior and life decisions of Generation Z. Data from the Central Statistics Agency (BPS) shows that the number of marriages in Indonesia has decreased from 2,016,171 events in 2018 to 1,478,302 events in 2024. This phenomenon encourages the need to study the relationship between economic uncertainty, financial anxiety, and the decision to marry from an Islamic economic perspective. This study uses a qualitative approach with library research and descriptive analysis methods. Data were obtained from publications from the Central Statistics Agency (BPS), government agency reports, books, and relevant scientific journals. Data analysis was conducted using content analysis techniques to identify factors influencing the decline in marriage rates in Indonesia. The results show that economic uncertainty characterized by high living costs, job instability, and increasing financial demands are the main factors driving Generation Z to delay marriage. These conditions also increase financial anxiety and create the phenomenon of Marriage is Scary, namely the perception that marriage is a decision full of economic and social risks. This study demonstrates that an Islamic economic perspective offers a more comprehensive understanding of this phenomenon by positioning marriage as part of worship, family resilience, and social well-being. The research findings demonstrate that economic, psychological, and spiritual aspects are interconnected in influencing marriage decisions among Generation Z in Indonesia.